Odpowiedź :
Odpowiedź:
x-3 = -2
x= 1
spr... 1-3= - 2
-2= - 2
L=P
3x-8= 1
x=3
spr... 3*3-8= 1
9-8= 1
1=1
L=P
5= 2x-1
x=3
spr... 5= 2*3-1
5= 6-1
5=5
L=P
-5 = 2x-1
x= - 2
spr... - 5 = 2*(-2)-1
-5= -4-1
-5= - 5
L=P
-2x - 3 = -5
x= 1
spr.. -2*1 -3= - 5
-2-3= - 5
-5= - 5
L=P
3x+8= - x
x= -2
spr... 3*(-2) + 8= - (-2)
- 6 +8= 2
2=2
L=P
zad.4
5x+7= 27
5x= 27-7
5x= 20 /:5
x=4
spr... 5*4+7= 27
20+7= 27
27=27
L=P
6x - 19= 5
6x= 5+19
6x= 24 /:6
x=4
spr.. 6*4 -19=5
24-19=5
5=5
L=P
10= 3x-2
10 +2= 3x
12 :3= x
4=x
spr.. 10 = 3*4 -2
10= 12-2
10=10
L=P
3= -5 + 2x
3 +5= 2x
8= 2x
8:2=x
4=x
spr.. 3= -5 + 2* 4
3= -5+8
3= 3
L=P
Szczegółowe wyjaśnienie: